Modelling a kinetic deviation of the magnesium hydrogenation reaction at conditions close to equilibrium. (8th November 2019) - Adams, Marcus; Grant, David M.; Stuart, Alastair; Walker, Gavin S.
Abstract: A model has been derived for the magnesium hydrogenation reaction at conditions close to equilibrium. The reaction mechanism involves an adsorption element, where the model is an extension of the Langmuir adsorption model. The concept of site availability (σs ) is introduced, whereby it has the capability to reduce the reaction rate. To improve representation of σs, an adaptable semi-empirical equation has been developed. Supplement to the surface reaction, a rate equation has been derived considering resistance effects. It was found that close to equilibrium, surface resistance dominated the reaction. Highlights: Magnesium sorption at close to equilibrium was described by a rate law of order 5/3. The site availability concept is proposed to represent hydrogenation reactions. Increasing the rate by improving heat transfer is represented by site de-activation. Diffusion resistance is negligible at conditions close to equilibrium.